Kwentong bakwit a video documentary series on bakwit school to educate and encourage undergraduate students to volunteer, donate, and advocate for the Lumad people's cause - Paderes, Sofia A.; Sicat, Jose Manuel (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Since President Duterte's declaration of Martial Law in Mindanao in May 2017, the increased attacks Lumad schools have forcibly displaced Lumads, the non-Muslim indigenous Mindanawon groups, from their own communities. This resulted in their evacuation to Metro Manila and the establishment of Bakwit School. The Lumads are in Metro Manila not only to learn in a safe space but to educate the public on their plight and call them to action.

Bakwit, originally referring to the Tagalog translation of "evacuee" or "to evacuate", now carries a political connotation to the Lumads who have been forcibly displaced. Save Our Schools Network adopted the term and now defines Bakwit School as, "...a makeshift school for displaced indigenous children. The Bakwit School is an assertion of the Lumad children's right to education despite the real threats and dangers they face in their communities." The Bakwit School is a mobile school and is constantly in need of housing and volunteers. Because the Bakwit School is regularly housed in universities, this research primarily targets undergraduate college students from different universities in Metro Manila aged 17-21. The secondary target audience are fresh graduates who aren't working yet, and are looking for a fulfilling avenue to use their skills and education.

This study aims to educate undergraduate students on the negative effects of Martial Law in Mindanao, and encourage their support for Bakwit School through volunteering, donating, and advocating for their cause.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 70-73
Keywords: Lumad (Philippine people) -- Documentary films; Refugee camp schools -- Metropolitan Manila (Philippines) -- Documentary films; Student movements